Cellular structure and chemical composition of cork from the Chinese cork oak (Quercus variabilis) - Miranda, Isabel; Gominho, Jorge; Pereira, Helena (Journal of Wood Science, 2012)
Quercus variabilis Blume, the Chinese cork oak, is an oak species with a thick cork outer bark. The cork is exploited at a limited scale in China and considered of lower quality than the commercial cork from Quercus suber. We studied an industrial cork granulate feedstock of Q. variabilis in relation to cellular structure and chemical composition and compared it to Q. suber cork under a material’s perspective. The cork of Q.variabilis has 1.1 % ash, 9.6 % extractives, 34.8 % suberin and 19.1 % lignin. The monosaccharide composition with shows a predominance of hemicelluloses: glucose 42.8 % of total neutral sugars, xylose 27.5 %, arabinose 15.4 %, galactose 9.0 %, mannose 4.0 %, rhamnose 1.2 %. The FT-IR spectrum shows the indicative peaks of suberin. The composition is overall similar to that of Q. suber cork. Q. variabilis cork has the typical cellular characteristics of bark cork tissues with a regular and radially aligned structure of cells without intercellular voids. Solid volume fraction was estimated at approximately 16 %. Compared with Q. suber, the Q. variabilis cork cells are smaller, the cell wall undulation and the overall row alignment less homogeneous, the cell surface is irregular and the solid volume proportion higher. The characteristics of Q. variabilis cork support its use as a cellular material for sealing, insulation and energy absorption, but the overall quality is lower than that of Q. suber cork. The negative impact of the higher density and structural lower uniformity at tissue and cell level should be evaluated for processing and product performance.
Keywords: Cellular structure; Cork; Quercus suber; Quercus variabilis; suberin

Temperature-induced structural and chemical changes in cork from Quercus cerris - Şen, Ali; Miranda, Isabel; Pereira, Helena (Industrial Crops and Products, 2012)
The effects of temperature on anatomical and chemical characteristics of Quercus cerris cork were examined. Cork samples were subjected to isothermal air heating between 150 ◦ C and 400 ◦ C and analyzed for mass loss, cellular structure and chemical composition. The thermal decomposition of Q. cerris cork is similar to that of Q. suber cork. Cork is thermally stable below 200 ◦ C and after that degradation depended on temperature and heating time with increasing mass loss, i.e. 3% at 200 ◦ C 10min and 46% at 350 ◦ C 60min.With temperature and starting at 200 ◦ C, cells expanded, cell wall thickness was reduced and corrugations were lost. Extractives degraded at lower temperatures, although aliphatic extractives were found to be more stable. Suberin from Q. cerris was more heat resistant than Q. suber suberin, while lignin showed similar resistance. These results provide a basis for studies on the production of Q. cerris bark expanded cork agglomerates for insulation purposes.
Keywords: Cellular structure; Cork; Quercus cerris; suberin; Temperature

The cellular structure of cork from Quercus cerris var. cerris bark in a materials’ perspective - Şen, Ali; Quilhó, Teresa; Pereira, Helena (Industrial Crops and Products, 2011)
Cork in the outer bark of trees is among the valuable raw materials of biological origin due to properties that result mainly from its cellular structure. Large scale commercial utilization of cork has been only achieved with cork from Quercus suber. Another oak species, Quercus cerris, also contains substantial, albeit not continuous, regions of cork that are clearly visible to the naked eye but are so far considered as a waste material. Bark samples of Q. cerris var. cerris trees were collected from the Andırın province, Turkey. Cork portions were separated and their cellular structure was investigated with optical and electron scanning microscopy observations. The results were compared with Q. suber cork. Q. cerris cork has the typical features of cork tissues with a regular and radially aligned structure of suberized cells without intercellular voids, showing a ring structure and a distinction of earlycork and latecork cells. Solid volume fraction was estimated at 25% (22% in earlycork, 36% in latecork). In Q. cerris cork cells are smaller, cell wall thickness and solid volume fraction are higher, and the tissue is less homogeneous with a higher content of ligniﬁed inclusions than in Q. suber cork. These factors will negatively inﬂuence quality in regard to density and mechanical properties associated to elasticity. However, this does not impair its use for production of granulates and agglomerates, e.g. for insulation and energy absorption. Separation of the cork fraction from the bark is a step required before further processing and use.
Keywords: Bark; Cellular structure; Cork; Quercus cerris; Quercus suber

The thermochemical degradation of cork - Pereira, H (Wood Science and Technology, 1992)
. The thermochemical degradation of cork from Quercus suber L. was studied in the temperature range 150 ~ ~ in relation to mass loss, chemical composition and the influ- ence on the cellular structure. The degradation of cork is strongly dependent on temperature and mass losses become significant at 200~ (15% of initial dry weight) and increase rapidly for higher temperatures (27% at 250 ~ 49% at 300 ~ 62% at 350 ~ until ashing at 450 ~ The polysaccharides are the most heat sensitive components: at 200 ~ hemicelluloses disappear and cellulose is degraded to a considerable extent. Suberin is more resistant and degradation starts at approx. 250~ 300~ samples only contain 7% suberin. The cellular structure of cork is also significantly influenced by temperature. Upon heating, cells expand and the cell walls stretch, attaining at 250~ a maximum cell volume increase corresponding to a factor of approximately 2. Above 300 ~ the structure of cell walls is considerably changed and show profound physical damage; in the later stages of pyrolysis, a cellular structure is no longer observed.
Keywords: Cellular structure; Cork; mass loss (voyant); thermochemical degradation